Heavy Metal Toxicity of Pb in the Organs of Nile Tilapia (Oreochromis Niloticus) in the Watershed Due to Hospital Waste - Nindha Ayu Berlianti; Yuda Cahyoargo Hariadi; Arry Yuariatun Nurhayati; Wenny Maulina; Firda Fadri (Universitas Pendidikan Ganesha, 2024)
The toxicity levels of heavy metals accumulated in water and sediment due to hospital waste discharge not only impact the environment but also pose a significant threat to human health. Long-term accumulation of these metals in the body may lead to degenerative diseases such as cancer. This concern highlights the urgency of conducting laboratory-based experimental research to identify the distribution of heavy metals in aquatic environments caused by hospital waste. The study employs Nile tilapia (Oreochromis Niloticus) as a bioindicator, a species capable of absorbing metals through its tissues. The research subjects consisted of 35 Nile tilapia with a body length of 8–12 cm and a weight of 12–15 grams, alongside hospital waste samples collected from three discharge points. Data collection methods included sample preparation of both hospital waste and Nile tilapia, treatment with varying concentrations of lead nitrate (Pb(NO3)2), and maintenance durations of 7, 14, 21, and 28 days. The concentration of Pb in the gills and muscle tissue of the fish was measured using Atomic Absorption Spectroscopy (AAS). The analytical data, represented as heavy metal concentrations, were plotted on a graph showing the relationship between concentration variations and maintenance durations and analyzed using One-Way ANOVA with nonparametric Tukey's test. The analysis revealed that the highest Pb concentration was observed in the gills of Nile tilapia on day 28 at 1.57 ppm, while the Pb concentration in muscle tissue reached 0.25 ppm on day 21. According to BPOM standards, Pb levels in Nile tilapia muscle tissue remain within the safe consumption threshold (≤0.3 ppm), whereas Pb levels in the gills exceeded the tolerance limit. This study provides scientific evidence on the risks of heavy metal accumulation in aquatic biota due to hospital waste and underscores the importance of improved waste management practices to safeguard public health and the environment.